The Phenomenon of Bearish and Bullish in The Indonesian Stock Exchange - Berto Usman (Esensi: Jurnal Bisnis dan Manajemen, 2016)
The Phenomenon of Bearish and Bullish in The Indonesian Stock ExchangeBearish and bullish pattern commonly exist in any of stock exchanges all over the world. Hereby, the volatility of price on specific stock and index will generally perform a typical co-movement. This study is officially intended to reveal the existence of bearish and bullish phenomenon in Indonesia stock exchange. The technical tool used in this study was known as candlestick analysis. It is utilized to discover the inclination of price movement and the percentage of bearish and bullish shown by the index. Further, it is noted that the object of this study is Indonesia stock exchange, which is surrogated by IDX Composite (IHSG). This research finally proved that there were 61 bearish (38.85%) and 96 time bulish (61.15%) patterns in IDX Composite (IHSG).DOI: 10.15408/ess.v6i2.3750